The plague in iberian epidemic regiments (14TH century) - da Conceição Fagundes, Maria Dailza (2023)
In the context of the pestilence, in the 14th century, there was the production of several Epidemic Regiments, writings in which precepts aimed at the community were predominant, with the purpose of informing how to prevent against the plague. Our focus is the comparative study of two works produced in Iberian spheres by Christian and Arab physicists: the Regiment of pestilence preservation by Jacme d'Agramont and the Treatise on the plague by Ibn Jatima. In this perspective, this text aims to discuss the plague in these two medical writings from a comparative study about the definition of plague, the causes and the symptoms.